2003
DOI: 10.1093/jn/133.7.2225
|View full text |Cite
|
Sign up to set email alerts
|

Food Stamp Program Participation is Positively Related to Obesity in Low Income Women

Abstract: This study examined the relationship between Food Stamp Program (FSP) participation and the obesity of low income individuals using data from the National Longitudinal Survey of Youth 1979. Obesity was defined as body mass index >or= 30 kg/m(2). The data were arranged as a panel with multiple observations per individual, and the models of obesity included current and long-term FSP participation, additional demographic, socioeconomic and environment characteristics and individual fixed effects. Individual fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
8
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(167 citation statements)
references
References 23 publications
(43 reference statements)
5
145
8
9
Order By: Relevance
“…21 Indeed, mounting evidence suggests that the Supplemental Nutrition Assistance Program may be associated with increased body mass index (BMI) for adult women. [22][23][24][25] To help inform this debate, we examine new data on young children, ages three and five, who constitute a primary target population for the various federal food assistance programs. Children may receive food assistance through multiple federal programs during early childhood, and each program may have a unique effect on children's weight.…”
mentioning
confidence: 99%
“…21 Indeed, mounting evidence suggests that the Supplemental Nutrition Assistance Program may be associated with increased body mass index (BMI) for adult women. [22][23][24][25] To help inform this debate, we examine new data on young children, ages three and five, who constitute a primary target population for the various federal food assistance programs. Children may receive food assistance through multiple federal programs during early childhood, and each program may have a unique effect on children's weight.…”
mentioning
confidence: 99%
“…Although the current study did not control for selection bias toward participation in public assistance programs and was not able to identify which public assistance programs the women used, some studies have found a positive association between participation in the Supplemental Nutrition Assistance Program (SNAP) and higher BMI status in women. 21,[35][36][37] It has been suggested that families who are at risk of experiencing food insecurity have limited cash assistance to spend on food at the end of the month because the majority of SNAP benefits are used within the first 3 days of the month when SNAP benefits are distributed. 38 The sharp decline in cash benefits toward the end of the month leads to a reduction in food consumption among mothers, perhaps even starving themselves so that their children can have sufficient food to eat.…”
Section: Discussionmentioning
confidence: 99%
“…Variables include woman's age (years), marital status (1 = married, 0 = not married), race (non-Hispanic white [reference], Hispanic, and non-Hispanic black), education (1 = high school graduate or more, 0 = less than high school education), and household income based on the Federal Poverty Line (FPL) threshold (1 = ‡ 200% FPL, 0 = < 200% of FPL). Participation in public assistance programs (1 = yes, 0 = no) was included in the regression models, as public assistance programs, specifically the Supplemental Nutrition and Assistance Program, have been associated with elevating women's weight status, 21,22 although current research indicates that the effect may be small. 23 Minority individuals and individuals of low SES are more likely to have reduced access to care, 24 and reduced access to care minimizes assistance provided by clinicians to manage weight.…”
Section: Covariatesmentioning
confidence: 99%
“…8 Overall, the empirical literature has yielded mixed findings on the effects of participation in the FSP on body weight. Studies based on longitudinal data (e.g., Gibson, 2003Gibson, , 2006 suggest that 3 We use the term ''unhealthy" here to identify foods that are likely to be caloriedense and nutrient-poor, and hence not included on the list of allowable foods in the proposed FSP, and not meeting the requirements of the US dietary guidelines. We understand that most foods can be a component of a healthy diet if consumed in moderation, but we find it convenient to use this shorthand to indicate food that would no longer be subsidized under the proposed FSP.…”
Section: Intended and Unintended Consequences Of The Food Stamp Programmentioning
confidence: 99%
“…For example, the growing numbers of people who are categorized as obese and overweight are drawn from all socioeconomic, ethnic, and demographic groups, but not uniformly. Several writers have observed that low-income women-including those receiving food stamps-are more likely than the rich to be obese and overweight (Gibson, 2003;Townsend et al, 2001). This observation leads to two questions.…”
Section: Introductionmentioning
confidence: 99%